?Carrot and Citrus Juice Waste as Potential Source of Dietary Fiber - KHAN, MUHAMMAD RAUF; SUFI, N.A. (Biological Sciences - PJSIR, 1995)
There is a growing community awareness of the impor- . tance of an adequate intake of dietary fibers. There is a potential for many fruits, vegetables and cereal residues as dietary supplements and in food manufacture.